The Effect of Blended Learning-Based Problem-Based Learning on the Critical Thinking Ability of High School Students in Physics Subjects - Lasmiati, Yuyun; Herliana, Fitria; Syukri, Muhammad; Musdar, Musdar; Wati, Nurul; Hamid, Abdul (MJI Publisher, 2024)
Based on the demands of 21st century ability, it is hoped that students can master critical thinking skills, especially in physics learning, considering that physics is one of the parts of science learning that cannot be separated from the ability to think critically in solving phenomena in the universe. This research is a type of quasi-experimental research that aims to see the influence of the Blended Learning-based Problem Based Learning model on students' critical thinking skills. The approach used is a quantitative approach. The research population is students of class XI MIPA SMA Negeri Unggul Subulussalam with class XI MIPA 3 as the experimental class and class XI MIPA 4 as the control class. The instruments used are test instruments, questionnaire instruments, observation instruments, and interview instruments. Based on the results of the t-test, a tcount value of 9.1493 was obtained with a ttable of 1.6735 which means that there is a significant difference between the experimental class taught using the PBL Learning model based on blended learning and the control class taught using the PBL learning model only. From the results of data analysis and discussion, it can be concluded that the blended learning based PBL learning model is one of the learning models that is able to improve the critical thinking skills of students at SMA Negeri Unggul Subulussalam